Description of the female and larval stage of Odontophotopsis succinea Viereck (Hymenoptera: Mutillidae), with new synonymy and notes - Pitts, James P.; Parker, Frank D. (Zootaxa, 2003)
Four specimens of Odontophotopsis succinea Viereck eclosed from cocoons of Oxybelus uniglumis (L.) (Hymenoptera: Crabronidae) collected in Davis, California. One specimen is a female and is described below. The larval stage is also described based on a larval exuvium. This record represents the second host record and the first descriptions of the female and the larva for Odontophotopsis. After study of the holotypes of several Odontophotopsis species by JPP, O. annulata Baker is synonymized with O. succinea Viereck.